Manejo poscosecha para el control de la enfermedad antracnosis en papaya (Carica papaya L.)” - Vera Araujo, David Alexander (2020)
Papaya is a crop little studied in Ecuador, its planted area is very little. Therefore, its management is very little known, for farmers who are dedicated to this crop it is a complete challenge. In the harvest and postharvest management, certain measures must be taken into account since it is a fruit susceptible to blows, which allow the anthracnose disease to appear easily. Harvesting is a high-care task, once it is in post-harvest is where the challenge for farmers begins. In post-harvest, the fruit must be treated with a process just like the banana, once harvested the fruits take the plant to a washing process with a chlorinated solution, from there they are submerged for a few minutes in water with fungal solutions. Once the fruit goes through these two treatments, it is necessary to pack them in boxes wrapped with paper so that there is no friction between them or blows where a wound and the Colletotrichum gloeosporioides fungus can be caused, and thus the fruit can be lost. The Colletotrichum gloeosporioides fungus is the cause of the anthracnose disease that once it enters the fruit is difficult to control, so the aforementioned preventive measures are taken. The chemical control is carried out in the pools where the fruit is submerged for a few minutes to give it its respective treatment and clean the fruit, many of the farmers to save do not carry out this treatment and then are affected when they lose the fruits due to the anthracnose disease.